Increasing green infrastructure-based ecological resilience in urban systems: A perspective from locating ecological and disturbance sources in a resource-based city. (October 2020) - Wu, Xia; Zhang, Jianjun; Geng, Xiaoli; Wang, Tong; Wang, Ke; Liu, Shidong
Highlights: Ecological resilience theorical model was proposed for resource-based city. Theoretical ecological corridors are determined based on the MCR model. The construction scheme is put forward to provide reference for resilience growing. Abstract: Maintaining the sustainability of the ecosystem in an ever-changing environment and enabling it to continuously provide services for human beings has become the focus of managers. Resilience is considered the key to maintaining the sustainability of an ecosystem. This paper combines source-sink landscape theory, on the basis of considering ecological processes, and builds a framework of factors that affect the ecological resilience of resource-based cities. We used Wu'an, a typical resource-based city, as the study area, and identified the ecological and disturbance sources to determine the ecological resilience. Green infrastructure (GI), as a kind of ecological infrastructure, plays a critical role in growing resilience. Our study established ecological corridors using the minimum cumulative resistance (MCR) model. And then provides a way in time and space to improve resilience based on corridors' internal and external conditions. Moreover, in the context of development where ecological protection is a priority and construction land expansion are limited, this method can assist government decision-making and serve to delineate the boundaries of urban development and the scope of mining activities.